Characterizing and Evaluating Integrated Landscape Initiatives - Carmenta, R.; Coomes, David A.; DeClerck, Fabrice A.J.; Hart, A.K.; Harvey, C.A.; Milder, J.; Reed, J.; Vira, B.; Estrada-Carmona, Natalia (Elsevier, 2020)
Sustainability agendas increasingly recognize that attaining conservation and development outcomes demands greater integration across sectors. Integrated landscape initiatives (ILIs) are a leading approach to reconciling multiple objectives. However, a characterization of the diversity of approaches under the ILI umbrella and the comparative performance of different types of approach is lacking. Here, we analyze questionnaire data obtained from project proponents to delimit four particular types of ILI: one type was dominated by agricultural interventions and another by conservation interventions, and these partially integrated ILIs engage local scales of governance; the remaining two types exhibit strong integration, with aims and actions across multiple sectors and scales of governance. We show that integrated projects were deemed to be more successful by project proponents. The typology offers the practitioner and research community an explicit set of strategies for selection, evaluation, and support and attests to the need for integration to achieve sustainable outcomes.